Faults and reals releated to pain [Aǧriya i̇lişkin Yanilgilar ve Gerçekler] - (:unkn) unknown (My University, 2002)
Although nurses and other health care professionals are paying more attention to pain control than over before, too many patients still suffer needlessly. The one reason is that health care professionals don't know enough about relieving it and don't team work; another is that many patients underreport pain. In this article is discussed faults and reals related to unrelieving pain.